Contribution of Smokeless Chulha for Rural Cooking in Churachandpur District, Manipur - Devi, S. Roma; Singh, L Kanta (Indian Journal of Hill Farming, 2018)
The smokeless chulha is a cooking stove that can save the lives of hundred thousands of women and young girls in rural areas as well as urban areas who are burning wood as cooking fuel. Average time required to boil one litre of water was calculated 12.25 minutes using smokeless chulha and in case of traditional chulha it was 19.3 minutes. Average fuel require to boil one litre of water was estimated 237 gm of fuel wood for smokeless chulha and whereas 411 gm of fuel wood was required in case of was traditional chulha. Smokeless chulha on an average could save 42.46% of fuel over the traditional chulha. The smokeless chulha could save huge amount of natural resources by reducing the cutting of forest.